The emerging role of Clostridium histolyticum collagenase in the treatment of Dupuytren disease - Alexis Thomas; Ardeshir Bayat (Dove Medical Press, 2010)
Alexis Thomas1, Ardeshir Bayat1,21Plastic and Reconstructive Surgery Research, School of Translational Medicine, University of Manchester, Manchester Interdisciplinary Biocentre, Manchester, UK; 2Department of Plastic and Reconstructive Surgery, Manchester Academic Health Science Centre, University Hospital of South Manchester National Health Service Foundation Trust, Wythenshawe Hospital, Manchester, UKAbstract: Dupuytren disease (DD) is a common fibroproliferative disease of unknown etiopathogenesis affecting the palmar aponeurosis, causing reduced hand function and resulting in fixed flexion contractures of the digits. Current gold standard treatment for the management of DD is surgical excision involving removal of the affected palmar fascial tissue. However, there are potential complications associated with surgery as it is costly and a positive surgical outcome is often short-lived because the disease tends to recur. Therefore, there is growing interest in nonsurgical, outpatient-based treatments that could be quicker, cheaper, reduce morbidity, show a decreased rate of recurrence, and give DD patients an improved quality of life when compared with traditional surgical management. Of the available nonsurgical options, injectable Clostridium histolyticum collagenase (CHC) has received recent clinical interest. In this article, a brief overview of DD surgical and nonsurgical treatments utilized is given, followed by a detailed examination of the nine papers published to date on the use of CHC in DD (and similar fibrotic disorders). These papers have investigated safe and efficacious doses for the injection of CHC to treat palpable DD cords in adult patients and have shown significant short- to mid-term results for correction to near-full digital extension (≤5° extension) following CHC injection of DD cords. CHC has been shown to target the collagen-based DD cords while sparing surrounding neurovasculature, with a complication profile that appears comparable to that of the surgical methods currently utilized. In conclusion, clostridial collagenase is a novel nonsurgical treatment option of considerable potential in the management of DD when administered by specialist hand surgeons with detailed knowledge of the disease and the relevant anatomy. Nonetheless, there is a need for further data on long-term results, complications, and rate of recurrence with the use of this emerging treatment option.Keywords: Dupuytren contracture, enzymatic injection, fibrosis, nonsurgical treatment